A CROSS-SECTIONAL INFOVEILLANCE STUDY ON WIKIPEDIA WAS USED FOR ACCESSING MAMMOGRAM INFORMATION. - Agyekum, Isabella; Simba, Hannah; Moodley, Yoshan (Student’s Journal of Health Research Africa, 2024)
Background Wikipedia has emerged as a source of health information for patients and the public. The study aimed to identify trends in the use of Wikipedia to access information on mammograms and to assess the quality of this information. Methods This was a trend analysis of cross-sectional data, namely Wikipedia page views for mammogram-related searches between 2016 and 2022. Data was analyzed with descriptive statistics. Overall trends in page views were analyzed by year and month. Pairwise comparisons were assessed with Analysis of Variance (ANOVA) testing. The quality of mammogram-related information on Wikipedia was evaluated using Couto and Lope’s four quality assessment features (Completeness, authority, informativeness, and consistency). Results The total number of page views for mammography-related terms during 2016-2022 was 1 180 947. The data fluctuated across years and months. When analyzed by year, mean page views peaked during 2018 (mean = 20 600.6) and were lowest during 2021 (mean = 10 267.9). When analyzed by month, mean page views peaked during March and October (means = 15 845.7 and 15 608.6, respectively). Overall, there were strong trends in page views across years (R2=0.99) and months (R2=0.73). The pairwise comparisons revealed numerous statistically significant differences in mean page views across years and months, which manifested as the observed polynomial trends. The quality assessment scores were as follows: Completeness (Medium), authority (Medium), informativeness (Low), and consistency (Medium). Conclusions Wikipedia is a potentially important source of mammogram information for patients and the public. This platform could be improved (diversity of page content and image presentation) and used to support public health awareness campaigns in combating breast cancer worldwide. Recommendation Efforts should be made to encourage the sustained use of Wikipedia by patients and the public as a source of mammogram information.